ChemInform Abstract: Indole‐benzodiazepine‐2, 5‐dione Derivatives from a Soil Fungus Aspergillus sp. PSU‐RSPG185. Issue 24 (2nd June 2014) - Rukachaisirikul, Vatcharin; Rungsaiwattana, Nachamon; Klaiklay, Saranyoo; Pakawatchai, Chaveng; Saithong, Saowanit; Phongpaichit, Souwalak; Borwornwiriyapan, Kawitsara; Sakayaroj, Jariya
Abstract Nine indole alkaloids were isolated from the title fungus including six new compounds [(I)‐(III)] called asperdiazapinones A‐F.